System of exercises to achievement the success during the attack in inferiority number lapses from The Handball Girls Team (14 - 16 age) of the EIDE "Ormani Arenado Llonch" in Pinar del Río - Yarisel Quiñones Rodríguez; Yailín Quiñones Rodríguez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2012)
This work is based on the difficult to keep the ball by the handball girls team (14-16 age) and been effective during the offensive in the inferiority number lapses. It is began from the empirical, theoretical and statistical methods, as the observation, interview and survey, also analysis- synthesis, historical- logical, inductive-deductive and descriptive statistical, in special mode the arithmetic average to procedure the results. After applying the instruments and consulting the bibliography about this subject, in national and international contents, it was elaborated a system of exercises considering the athletes characteristics to settling a real team's difficulty.